(untitled) (Ustozlar uchun, 2026)
This article examines the morphological structure of English and Uzbek verbs from a comparative linguistic perspective. The study focuses on the ways grammatical meanings such as tense, aspect, voice, mood, person, and number are expressed in the two languages. English, as an analytic language, relies heavily on auxiliary verbs and word order, whereas Uzbek, as an agglutinative language, primarily uses affixation. Through comparative analysis, the paper highlights both typological differences and functional similarities between the verbal systems of English and Uzbek.